Role of resilience in healthcare workers' distress and somatization during the COVID‐19 pandemic: A cross‐sectional study across Flanders, Belgium - Erik Franck; Eva Goossens; Filip Haegdorens; Nina Geuens; Michael Portzky; Tinneke Tytens; Tinne Dilles; Katrien Beeckman; Olaf Timmermans; Stijn Slootmans; Bart Van Rompaey; Peter Van Bogaert (Wiley, 2022)
Abstract Aim To evaluate the impact and the possible role of psychological resilience in the COVID‐19 pandemic outbreak on healthcare workers' mental and physical well‐being in Belgium. Design This cross‐sectional, survey‐based study enrolled 1376 healthcare workers across Belgium from 17 April 2020 to 24 April 2020. Methods The study sample consisted of direct care workers (nurses and doctors), supporting staff and management staff members. The main outcomes are resilience, distress and somatization. Results Higher educational level was associated with lower symptoms of distress and somatization. Physicians exhibited the lowest risk of experiencing heightened levels of distress and somatization. Controlling for confounding factors, higher levels of resilience were associated with a 12% reduced chance of increased distress levels and 5% lower chance of increased somatization levels. Our results suggest the potentially buffering role of mental resilience on those working on the frontline during the COVID‐19 pandemic outbreak.